Highlighting the Importance of Water Alkalinity Using Phosphate Buffer Diluted With Deionized, Double Distilled and Tap Water, in Lowering Oxidation Effects on Human Hemoglobin Ozonated at High Ozone Concentrations in vitro - Mehraban, Fouad; Rayati, Saeed; Mirzaaghaei, Vahid; Seyedarabi, Arefeh (Frontiers in Molecular Biosciences, 2020)
In autohemotherapy, it is important to find a way to lower the effects of oxidation, especially at high concentrations of ozone. One of the parameters, other than ozone concentration, which can have a significant effect on the stability and rate of decomposition of ozone at high concentrations, is the presence of ions in different types of water. Ion analysis of various types of water including deionized, double distilled and tap water along with phosphate buffer and a number of spectroscopic techniques including intrinsic fluorescence, circular dichroism and UV–VIS spectroscopies were used as well as SDS-PAGE, Native-PAGE and dynamic light scattering to investigate the effects of two relatively high concentrations of ozone on purified human hemoglobin (Hb) in phosphate buffer and that diluted with various types of water in vitro. Purified human Hb and not whole blood human Hb was used in this study, since the addition of water to the whole blood would have caused the RBCs to lyse, affecting the purification of Hb for further analysis. Therefore, using purified Hb, it was possible to investigate the effects of dilution of 50 mM phosphate buffer to 10 mM phosphate buffer with different water types including non-ion containing deionized and double distilled waters as well as ion-containing tap water, when ozonated at 55 and 80 μg/ml ozone. The fundamental changes in the secondary and tertiary structures of Hb were seen to be related to non-ozonated Hb samples diluted with deionized and double distilled waters, respectively. Generally, Hb oligomerisation was more likely to occur at the higher concentration of ozone (80 μg/ml) and in samples where phosphate buffer was diluted with non-ion containing deionized and double distilled waters and not the ion-containing tap water. This could be explained by the presence of water alkalinity or bicarbonate ions in tap water, which can scavenge free radicals and reduce Hb oxidation/oligomerisation. Therefore, it was concluded that Hb could best withstand high concentrations of ozone in the presence of the undiluted 50 mM phosphate buffer followed by the presence of phosphate buffer diluted with tap water, containing bicarbonate ions.